Impact of complex hydromechanical treatment on the size of particles of plant raw materials in the fuel ethanol technology - Obodovych, Oleksandr; Bulii, Yurii; Sydorenko, Vitalii; Parchenko, Volodymyr; Khomenko, Valentyna (My University, 2025)
The main disadvantage of ethanol production from lignocellulosic raw materials is the high cost due to the presence of hemicelluloses and lignin. Considering the peculiarities of structural and chemical factors that determine its resistance to the action of enzymes, a necessary stage in the technology of obtaining ethanol for the next generation is the stage of pretreatment for hydrolysis.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; паливний етанол; попередня підготовка; лігнін; імпульси тиску; реактор-змішувач; fuel ethanol; pretreatment; grinding; hydromechanical processing; reactor mixer